Research and application of locomotive automatic operation technology - SHANG Jing; LIU Yong; JIANG Fan (机车电传动)
In the current development tide of rail transit towards green and intelligence, automatic operation technology plays a role in the control basis for the orderly and coordinated operation of trains under the future railway network conditions, and emerges as a typical representative of the rail transit development in the field of intelligent technology, thanks to the benefits to further improving the efficiency while reducing the energy consumption of train operation, eliminating the operation differences among drivers, and raising the consistency of train operation. This paper analyzed the current development and technical difficulties of locomotive automatic operation research in China and abroad, elaborated the overall architecture of the locomotive automatic operation system to meet the application requirements on the trunk lines in China, proposed a manned locomotive automatic operation design, with details on the key technologies such as train operation planning and speed control, train simulation in longitudinal dynamics, multi-sensor fusion perception, operation simulation of train systems, and was concluded with ideas and prospects on the future development trends of automatic locomotive operation technologies. The locomotive automatic operation system based on the above-mentioned technologies has been used in many CR regional groups and turned out with remarkable application results. The system can support different formations and loads, and is adaptive to different car models, control systems, and signal systems, demonstrating good universality and popularization.